(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2021)
Introduction: Open fractures are known orthopaedic emergencies associated with healing problems and risk of infection. The open fractures are common cases because of motor vehicle and motorbike accidents, falls from height and sometimes gun-shot wounds. Significant morbidity and subsequent disability may happen, if not managed properly. Aim: To evaluate the pattern of open fractures associated with healing problems and achieving sound bone union, avoiding infection and regaining full functional recovery of the limb. Methods: This retrospective study included all the patients who were hospitalized with open fractures of lower limbs in a United Nations Level II Hospital of Bangladesh Medical Contingent at Kaga-Bandoro in Central African Republic from April 2015 to November 2018. Results: There were 57 patients with open fractures resulting 17.8% of total trauma patients. The mean age was 31.8±11.6 years. Most patients were in the 20-39 years age group. The male to female sex ratio was 4.2:1. Road traffic accident was the main cause of open fractures (59.6%). Fractures of tibia-fibula and femur contributed 49.1% and 15.7% respectively and 89.4% satisfactory results were achieved after treatment. Conclusion: The management of open fractures presents a challenge due to risk of infection, healing problems and subsequent morbidity. Adequate debridement and copious lavage remains one of the cornerstones of management of open fractures. The initial management of open fractures affects the ultimate outcome. JAFMC Bangladesh. Vol 15, No 1 (June) 2020: 50-53